Significantly Increased Risk of All-Cause Mortality Among Type 2 Diabetes Patients Living Alone - Fu, Liyao; Zhou, Ying; Sun, Jiaxing; Xing, Zhenhua; Wang, Yongjun; Tai, Shi (Frontiers in Medicine, 2022)
BACKGROUND There is a lack of studies evaluating the association between living status and subsequent outcomes in patients with type 2 diabetes (T2DM). OBJECTIVES This study aimed to assess the association between living alone and the risk of all-cause mortality in T2DM patients. METHODS We used data from the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial. The primary outcome was all-cause mortality. We analyzed and compared the hazard ratios (HRs) in patients living alone and with one or more adults, using multivariable Cox proportional hazard models. RESULTS: This study included 10,249 T2DM patients. Of these, 2,078 (20.28%) were living alone and 8,171 (79.72%) lived with one or more adults. Over a median total follow-up of 8.8 years, 1,958 patients developed the primary endpoint. The all-cause mortality rates in patients living alone or living with one or more adults were 23.24% and 18.05%, respectively. Cox proportional hazard analysis showed that T2DM patients living alone had a significantly higher rate of all-cause mortality than those living with others (HR, 1.34; 95% confidence interval [CI], 1.20-1.48; p<0.001). After multivariable adjustment, living alone was an independent risk factor for all-cause mortality in patients with T2DM (adjusted HR, 1.27; 95% CI, 1.14 to 1.41; p<0.001). Furthermore, the risks of both congestive heart failure (CHF) and fatal coronary heart disease (CHD) among 4,050 propensity score-matched patients were higher for patients living alone (respectively HR, 1.37; 95% CI, 1.08-1.74; p = 0.010; and HR, 1.16; 95% CI, 1.00-1.34; p = 0.047). CONCLUSIONS: The risk of all-cause mortality was significantly higher in T2DM patients living alone than in those living with one or more adults.